Shuttle‐Mediated Nanoparticle Delivery to the Blood–Brain Barrier. Issue 6 (7th November 2012) - Guarnieri, Daniela; Falanga, Annarita; Muscetti, Ornella; Tarallo, Rossella; Fusco, Sabato; Galdiero, Massimiliano; Galdiero, Stefania; Netti, Paolo A.
Abstract Many therapeutic drugs are excluded from entering the brain due to their lack of transport through the blood–brain barrier (BBB). The development of new strategies for enhancing drug delivery to the brain is of great importance in diagnostics and therapeutics of central nervous diseases. To overcome this problem, a viral fusion peptide (gH625) derived from the glycoprotein gH of Herpes simplex virus type 1 is developed, which possesses several advantages including high cell translocation potency, absence of toxicity of the peptide itself, and the feasibility as an efficient carrier for delivering therapeutics. Therefore, it is hypothesized that brain delivery of nanoparticles conjugated with gH625 should be efficiently enhanced. The surface of fluorescent aminated polystyrene nanoparticles (NPs) is functionalized with gH625 via a covalent binding procedure, and the NP uptake mechanism and permeation across in vitro BBB models are studied. At early incubation times, the uptake of NPs with gH625 by brain endothelial cells is greater than that of the NPs without the peptide, and their intracellular motion is mainly characterized by a random walk behavior. Most importantly, gH625 peptide decreases NP intracellular accumulation as large aggregates and enhances the NP BBB crossing. In summary, these results establish that surface functionalization with gH625 may change NP fate by providing a good strategy for the design of promising carriers to deliver drugs across the BBB for the treatment of brain diseases.